Effect of economic integration on agricultural export performance in selected West African countries - Olatunji Abdul Shobande (Economies, 2019)
The paper investigates the effect of economic integration on agricultural export performance in West African economies using the gravity model of bilateral trade on the annual time series data straddling the period 1970 to 2016. The empirical evidence is based on the pooled OLS and fixed effects estimator. We find that economic integration, as measured by trade openness, is a remarkably strong predictor of export performance in the region. We also examine the effect of geographical distance measured by effective nominal exchange rates and we find it has a negative effect on agricultural export performance. The paper recommends the adoption of a common currency to help mitigate exchange rate negativity that serves as resistance to trade in the region. Likewise, proactive agricultural research, extension and market driven strategies are strongly advocated for driven competition and economic efficiency within the regional agricultural sector.
Keywords: F12; Q14; Q17; 330; agricultural; economic integration; export; West Africa